Physicochemical properties of pea proteins, texturization using extrusion, and application in plant-based meats - Webb, Delaney Madeline (Kansas State University, 2021)
With a growing trend for plant-based and clean label products, extrusion texturization of pea protein is becoming more prevalent for plant-based meat applications. However, several challenges have surfaced from this. Large demand for pea protein has made sourcing difficult and expensive. Differences in the physicochemical traits of pea protein compared to traditional textured vegetable proteins, wheat and soy, mean that final product traits are different when switching to pea protein. Additionally, pea protein from different suppliers is sourced and processed differently, and thus require different extrusion processing and lead to varying final product traits. The intent of this research was to better understand the differences between common and upcoming proteins used for texturization, the impact of formulating pea protein with legume flours and fibers, and how various pea proteins differ in raw material physicochemical traits and lead to differences in texturization. The first study invested how carbohydrate additions up to 20% affected pilot-scale twin screw extrusion and the pea protein extrudate properties. Characteristics of raw material, whole extrudate, and milled extrudate were observed. Adding pulse flour resulted in low water holding capacity (WHC) of the extrudates compared to the control of pea protein isolate (PPI) (241-391% and 496%, respectively). However, fiber increased the WHC from the pea flour treatment (428-442%). An increase in instrumental hardness was observed from PPI to all pulse flour treatments (475 g to 837-2333 g) due to the disruption of protein-networking and protein-based expansion. Both WHC and hardness have a strong relationship with the bulk density of the extrudate. Adding pulse flours to PPI in plant-based meat was shown to increase density and hardness of the extrudate and decrease WHC. However, addition of fiber reduced the negative impact of starch, and could allow more flexibility in targeting specific qualities while reducing the protein costs and usage for plant-based meats. In the second study, twin-screw extrusion was used to texturized four pea proteins, as well as soy and wheat proteins for comparison. Pea proteins from commercial sources varied in their functional properties. Proteins that had higher water absorption capacity had the highest peak viscosity. These proteins also required the least specific mechanical energy during processing. Pea protein extrudates displayed similar hardness, chewiness, and springiness, but varied in these traits when formed in a patty. A single trait did not seem to be most impactful in the creation of certain extrudate characteristics, and thus further study should be conducted on understanding the role of multiple factors to create a model which balances the most important factors for desired textured protein outcomes. This research has proven the importance of understanding raw ingredient sources, composition, and pre-processing for extrusion of plant protein. Textured pea protein shows significantly different texture compared to soy and wheat, and internal structure varies between textured pea protein made with isolates with different functional properties. Even more, starch and fiber can be successfully utilized to reduce necessary protein content for texturized pea protein while simultaneously using a co-product and targeting unique product texture.
Keywords: Plant-based meat; Pea protein; Extrusion; Textured vegetable protein; Meat analog; Fiber